ANALISA PERBANDINGAN PANJANG ANTRIAN MENGGUNAKAN TEORI ANTRIAN DAN ANALISA GELOMBANG KEJUT DI LOKET KELUAR KENDARAAN KAWASAN MEGAMAS MANADO - Pane, Fanto Pardomuan; Rompis, Semuel Y. R.; Timboeleng, James A. (JURNAL SIPIL STATIK, 2018)
In the science of traffic engineering, there are many methods of measuring queues and delays. Some of these methods are queuing theory and shockwave analysis. From these two methods will be compared the most ideal characteristics to analyze the queue and delay. The Methods in this research used primary data collected from Megamas Area through by manual survey method to analyze shockwave and queuing theory. The results obtained the following conclusions: (1) The shockwave analysis at the exit gateway counter are formed by Greenshieldsâ€™s basic chart andÂ  present the queue length, total duration of the counter opening for the last vehicle entering the queue, and total duration from opening of the counter to the normal condition will increase linearly with increasing incidence duration, while the delay will increase exponentially. (2) In queue theory analysis, existing counters are still capable for serving the vehicles, this is obtained from the average value Ï <1 (eligible) only at certain periods that have value Ï> 1. Based on analysis, the service level on all counters are strongly influenced by the speed and accuracy of service door operators, readiness of reserve money for returns, readiness of drivers who will be out of the area, such as preparing money to pay retribution and admission ticket. (3) The queue theory analysis is easier to use to analyze the queue at the counter than the shock wave analysis. Shockwave analysis is more macro when using traffic parameters such as volume, speed of density and capacity of the road wherein the change of traffic flow due to the obstacle becomes a reference to analyze the shock waves. In the case of the exit gateway of the vehicle counter Megamas, the length of the road for queuing is very limited, and if the number of vehicle queue is too long until the intersection between segment A and segment B then speed in both segments will be affected due to queue. Eventually, queuing theory in analyzing the queue at vehicle counter in Megamas area is more effective and efficient to use.Â Keywords : shockwave, queue theory, queue length